Electrochemical model-based fast charging strategy for lithium-ion batteries with lithium plating constraints - Xu, Shaochun; Lyu, Chao; Ma, Jingyan; Sun, Qingmin; Du, Limei (Proceedings of SPIE, the international society for optical engineering, 2025)
With the widespread adoption of electric vehicles and smart electronic devices, lithium-ion batteries have become a research and application hotspot as high-performance energy storage systems. However, achieving fast charging for lithium-ion batteries remains a challenging issue. The pursuit of rapid charging often leads to lithium plating, causing irreversible damage to the battery. This paper first proposes a simplified wide-C-rate-range electrochemical model based on parameter correction. Under conditions of 20 °C and up to 4 C-rates, the model achieves a mean absolute error of less than 23mV in terminal voltage, enabling accurate high-rate simulations. Subsequently, a negative electrode overpotential (NEO) calculation equation is derived based on this model. Using this foundation, a PID-based algorithm dynamically adjusts the charging current in real-time, ensuring that the estimated NEO does not exceed a predefined threshold. This approach enables fast charging while preventing lithium plating.